"Soft Evangelism": Reimagining faith-sharing in the Uniting Church - Kreminski, Karina (Uniting Church studies, 2025)
The ambivalence around the term "evangelism" in the church today is particularly true within the Uniting Church in Australia (UCA). Many people in the UCA feel awkward about the practice of evangelism in our secular culture which carries unhelpful "baggage" from Christendom. This presents a barrier for Christians who have "good news" to share with those who do not identify as Christian. This article will explore the peculiarities of the theory and practice of evangelism (or "witness") in the UCA, drawing on UCA theology and the Basis of Union. It will then employ a memoir theology approach, using a vignette and observations, to propose a way for UCA churches to engage in contextually appropriate evangelism in the liminal spaces between church and society, shaped by the peculiarities of UCA theology and practice. The result is a model of evangelism - "soft evangelism" - that can inspire UCA churches to reimagine faith-sharing in the Australian context.